Femilial Milia - Sarkar Rashmi; Thami Gurvinder P; Kaur Sukhjot; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2001)
Milia occurring in six individuals of a family is being reported for its rarity as familial occurrence. Differentiation from eruptive form of milia is being emphasized.